Polemic of Indian Government Deportation Policy Towards Rohingya - Erlangga, Alvin Ferian; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This article aims to explain why The Government of India in which have consistently implemented the policy of accepting refugees decided to deport Rohingya Refugees in 2018-2019. In this research there is an explanation of the facts that show the relation of refugee policies adopted by the Indian government and the phenomenon of deportation. This study uses a Post-Modernist framework with a Discourse Analysis approach. Based on the findings of this study it was revealed that the existence of deportation policy towards Rohingya refugees has a close relation with the discourse changes that occur due to the power-relations mechanism which involves the BJP government, right-wing Hindu groups, and the process of social cognition process from Indian Society.